PREMARITAL OF PRIVATE EDUCATION IN KANTOR URUSAN AGAMA (KUA) SEMARANG DISTRICT - Amat Mulyoko (Profetika: Jurnal Studi Islam, 2020)
Guidance of adolescent before marriage is carried out by Islamic Religious Instructor, Head and KUA Head. Islamic religious leaders guide mosque adolescents, prayer rooms and teaching assembly through routine or weekly teaching activities. The headman and head of the KUA carry out coaching for the bride and groom before the marriage ceremony. The lack of funds received by the KUA resulted in the implementation of the bride and groom course which caused the implementation to be not carried out to all prospective brides and responded by the KUA of Semarang regency through the private coaching of the bride and groom who wanted to carry out the wedding. This research is a qualitative analytic research and is a type of field research. Primary data sources, namely data obtained from interviews with the Office of the Ministry of Religion in Semarang, KUA in all districts of Semarang, and participants in premarital sex education, and secondary data in the form of books on marriage. Data collection methods are done by interview, documentation, and observation.